Exploring the design of interactive smart textiles for emotion regulation - Jiang, Mengqi; Bhömer, Martijn ten; Liang, Hai-Ning (Springer, 2020)
The present study aims to investigate the design of interactive textiles for emotion regulation. In this work we proposed a design which allows users to visualize their physiological data and help regulate their emotions. We used the Research through Design method to explore how physiological data could be represented in four different interactive textiles and how movement-based interaction could be designed to support users’ understanding and regulation of their emotional state. After an initial user interview evaluation with several textile prototypes, light and vibration were selected as modalities within the biofeedback-based interaction. A smart interactive shawl that reacts to changes in emotional arousal was designed to help the users know their emotion and adjust it, if necessary, with the support of electrodermal activity sensor and pressure-based sensors. The results of the second study showed that the smart shawl could help the user to visualize their emotions and reduce their stress level by interacting with it. © 2020, Springer Nature Switzerland AG.